Pembangunan Jalan Padang By Pass dan Dampak Sosial Ekonomi Bagi Masyarakat Sekitar - Emi Handrina (Jurnal Public Administration, Business and Rural Develoment Planning, 2019)
Jalan Padang By Pass is a development project carried out by the government in 1991 which was precisely carried out during the Repelita IV period. The Padang By Pass Road construction project was built to extend east of Padang City, from Lubuk Begalung Village to Duku Village, Pariaman Regency. The construction of the Padang By Pass Road was completed in 1993, which was marked by the opening of the Padang By Pass Road to the public. The construction of Jalan Padang By Pass has had an impact on the surrounding community. The impact of this development can not only be felt after the project is completed, but has been felt before the project is carried out, namely in the process of land acquisition. In the case of land acquisition, the government uses a method called land consolidation.